A Rough Colony Morphology of Mycobacterium abscessus Is Associated With Cavitary Pulmonary Disease and Poor Clinical Outcome - Hedin, Wilhelm; Fröberg, Gabrielle; Fredman, Kalle; Chryssanthou, Erja; Selmeryd, Ingrid; Gillman, Anna; Orsini, Letizia; Runold, Michael; Jönsson, Bodil; Schön, Thomas; Davies Forsman, Lina (The Journal of infectious diseases, 2023)
Abstract Background The Mycobacterium abscessus complex (MABC) is a difficult to treat mycobacterium with two distinct morphologies: smooth and rough. As the clinical implications are unclear, we explored the morphology of MABC in relation to disease and outcome. Methods We performed a retrospective multicenter cohort study including patients with confirmed MABC in Sweden, 2009–2020, with treatment outcome as the primary outcome. MABC colony morphology was determined by light microscopy on Middlebrook 7H10 agar plates. Results Of the 71 MABC isolates, a defined morphology could be determined for 63 isolates, of which 40 were smooth (56%) and 23 were rough (32%). Immunosuppression, pulmonary disease, and cavitary lesion on chest radiographs were significantly associated with a rough isolate morphology. Participants with smooth isolates had more favorable treatment outcomes (12/14, 86%) compared to those with rough isolates (3/10, 30%). In an age-adjusted logistic regression, rough morphology of MABC was associated to lower odds of clinical cure compared to smooth morphology (adjusted odds ratio, 0.12; P = .049). Conclusions Study participants with rough MABC colony morphology of isolates had a worse clinical outcome compared to those with smooth isolates. The biological mechanisms should be further characterized and colony morphology of MABC taken into account during clinical management. In this retrospective cohort study, a rough colony morphology of Mycobacterium abscessus complex was associated with poor treatment outcome, cavitary disease, and cough as a presenting symptom in the study participants, as compared to those with smooth isolates.